2019
DOI: 10.29356/jmcs.v63i3.627
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Characterization of LiMnPO4 Electrodes with Different Additions of MWCNTs in an Aqueous Electrolyte

Abstract: An electrochemical characterization was performed in electrodes with different weight percentages of LiMnPO4 and multi-walled carbon nanotubes (MWCNTs) in aqueous solution. The redox potential of LiMnPO4 cathode is close to the electrolyte decomposition, which provides an ideal scenario to study multiple reactions on a single electrode surface involving parallel steps and species transformation in both solid and liquid state. Different processes were deconvoluted using cyclic voltammetry and electrochemical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Here, "ss" means a surface site. The expression of the faradaic current is shown in Equation (13), while the relationship between the coverage factor and potential can be found from the dependency of the coverage with time in non-steady conditions (Equations ( 14)-( 17)) [43].…”
Section: Impedance Spectroscopy Modelingmentioning
confidence: 99%
“…Here, "ss" means a surface site. The expression of the faradaic current is shown in Equation (13), while the relationship between the coverage factor and potential can be found from the dependency of the coverage with time in non-steady conditions (Equations ( 14)-( 17)) [43].…”
Section: Impedance Spectroscopy Modelingmentioning
confidence: 99%
“…Other Mn‐based electrodes made short appearances, including MnO 2 40,41 and LiMnPO 4 42,43 . LiMnPO 4 reappeared briefly in 2019 with the addition of multiwall carbon nanotubes to the LiMnPO 4 cathode that increased the electrical conductivity of the cathode; however, cell impedance was unacceptably high and battery cycling was not attempted 44 . Notably, LiCoO 2 was also shown to perform as a cathode by Ruffo et al in 2009, 20 Yadegari et al in 2011, 45 and Ramanujapuram et al in 2016, 46 delivering nearly 100 mAh/g at industry‐relevant electrode loading levels of 3 mg/cm 2 or more of active material.…”
Section: Aqueous Lithium‐ion Batteries: the Early Daysmentioning
confidence: 99%
“…These results showed that the addition of CNTs to the active material can provide higher conductivity, a better rate performance, and also improve capacity retention during cycling by avoiding contact loss between active particles. J. Barraza-Fierro with co-authors [33] described the electrochemical behaviour of multi-walled carbon nanotubes (MWCNTs) in an acidic aqueous electrolyte (1 M LiNO 3 /HNO 3 with pH = 2) in the potential range of 0.4-1.4 V vs. Ag/AgCl. However, in this potential range (0.4-1.4 V vs. Ag/AgCl), lithium intercalation in MWCNTs did not occur, so it does not allow for the evaluation of the applicability of MWCNTs as an anode.…”
Section: Introductionmentioning
confidence: 99%